A study on Factors Affecting to the Chicken Layer’s Farm Business Operations of Entrepreneur in Luang Prabang Province - CHAMPASING, Souliya; DUANGVILAYKEO, Thipphavanh; KHOMTHAVONG , Phonepasith; SIFONGXAY, Sangthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
A study on factors affecting to the chicken layer’s farm business operations of entrepreneur in Luang Prabang Province aimed 1) to examine the chicken layer’s farm business operation of entrepreneur and 2) to explore factors affecting the chicken layer’s farm business operations of entrepreneur in Luang Prabang Province. The sample group was defined by Krejcie and Morgan (1970) and could obtain a total of 30 samples of laying hen and poultry farm in Luang Prabang Province. Through the process of collecting data from entrepreneurs the SPSS program was employed to obtain statistics of frequency, percentage, mean, and standard deviation and hypothesis testing of one-way ANOVA, T-test, Pearson Correlation, and multiple linear regression. result showed that the majority of respondents is male (80%); the largest proportion of each group was as follows: the age group between 46-55 years (36.70%), secondary school (60%), business experience between 5-10 years number of workforce between 1-5 person (43.30%), bank loans (76.70%), revolving capital between 50 million – 100 million (50%) and average monthly income 50 million - 100 million (43.33 %) and entrepreneurial factors related to the operating results of the chicken layer’s farm business by having revolving capital as an influence below 0.05 (P<0.05). The internal factors affecting to the results of the chicken layer’s farm business operations of entrepreneur in Luang Prabang Province consists of production and finance with a statistical significance level below 0.05 (P<0.05), and the chicken layer’s farm business operations of entrepreneur in Luang Prabang Province were not affected by the external factors